Shortage of Skilled Labor, Unions and the Wage Premium: A Regression Analysis with Establishment Panel Data for Germany - Arnd Kölling (Journal of Labor Research, 2022)
The author investigates the different influences of labor shortage on wages in firms with or without collective bargaining agreements. In addition to training, technological solutions, and organizational flexibility, employers can also offer higher wages at a constant employment level to fill vacancies if the current payments are lower than the marginal revenue of the workers. Firms with collective bargaining agreements probably already pay wages according to marginal revenue or, in the case of rent sharing, above it, and the remuneration is probably also not adjusted. Using wage regressions with panel data for German establishments, this paper shows that collective bargaining and a lack of skilled workers can lead to higher wages. However, the latter only applies to firms that are not bound by collective agreements. Hence, wage differentials between these firms decrease, providing further explanation for a countercyclical development of the wage premium from the collective bargaining agreement.
Keywords: J23; J24; J51; J63; 330; Shortage of skilled labor; collective bargaining; wage premium; classification; Economics